Measurement and recording of magnetics fields at high altitudes - Limón Díaz, Pedro Antonio; García Ballinas, Sirgei; García Ramírez, Mario Alberto (UANL. Facultad de Ingeniería Mecánica y Eléctrica, 2015)
When a land-air misile is fired to pursuit a mobil target, quite a few variables play a key role in order to reach and neutralise the target in no-time. It is desired; nevertheless, this system requires an amount of time, fuel, real-time data analysis as well as a discriminator system, all these in order to reach the mobil target. This is why, in this work we present a study for a set of variables meassured in situ such as: the wind speed, magnetic field, pressure and humidity to generate logs that can be usuful for either civil and militar applications. The system is designed to meassure in situ a set of variables starting at 500 m up to 30 km. As a result of this study, all the information gathered can be feed into the missil main computer and with the info loaded, it can trace trajectories in which the efficiency of the engine, fuel and cargo reach the target. The low atmosphere system has the follow set of instruments: a barometer, accelerometer, gyroscope and a magnetometer as the sensor array. We are using an Intel Galileo board as the motherboard. The information collected is saved within a SD high density memory card.